2020
DOI: 10.1007/s11249-020-01341-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hair Coverage and Sweating for Textile Friction on the Forearm

Abstract: Friction of textiles on the human forearm is an important factor in comfort sensations of garments. We built an experiment to measure friction for textiles sliding on the forearm under loading conditions which are characteristic for wearing shirts or jackets. The hair coverage of the participants’ forearm was quantified by image analysis of photographs of the arm in the region of contact. Friction results for five standard textiles suggest to treat hair coverage in two classes. Sweating after physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Sweating increases the friction of hairy arms to a large extent in comparison to the non-hairy arms. 16 Tribological study of human skin is also used to study the feasibility of skin care products concluding volar forearm to be independent of age, gender and ethnicity. 77 Skin hydration leads to skin softening that tends to increase in contact area and ultimately increasing the adhesion phenomena which is specific to gender.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sweating increases the friction of hairy arms to a large extent in comparison to the non-hairy arms. 16 Tribological study of human skin is also used to study the feasibility of skin care products concluding volar forearm to be independent of age, gender and ethnicity. 77 Skin hydration leads to skin softening that tends to increase in contact area and ultimately increasing the adhesion phenomena which is specific to gender.…”
Section: Discussionmentioning
confidence: 99%
“…Frictional behaviour of human skin with materials popularly used in prosthetic development is investigated through sclerometer considering factors such as hair on skin, sweat, skin moisture, indentation, interaction velocity etc. 14 Role of hair and sweating on the skin-textile frictional characteristics of forearm is studied 16 through experimental setup as shown in Figure 9. Studies having forearm as site of investigation are tabulated in Table 3.…”
Section: Volar Forearmmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the interface between wet fabric and skin have shown that the friction force increases as the interface becomes saturated with water [16]. Liu also reported that the presence of body hair on the skin reduces the friction effect when water is added, suggesting that its impact may depend on the geometry of the skin [17]. While some models have been proposed to explain the contact Toshiaki Nishi 1) *, Atsushi Matsumura 1) , Manami Koshida 2) , Tatsufumi Matsumoto 2) and Takeshi Yamaguchi 1,3) between fabric and skin [18,19], the mechanism underlying the substantial increase in friction when water is introduced remains unclear [20].…”
Section: Introductionmentioning
confidence: 99%